Collective creativity in STEAM Making activities - Timotheou, Stella; Ioannou, Andri (My University, 2021)
While some researchers have focused on the study of creativity in Making contexts, no work has so far documented learners’ collective creativity as they engage in Making projects. Research on the assessment of collective creativity in Making projects and the relationship between collective creativity and project success remains scarce. In the present investigation, we adopted a Making approach to teaching and learning in the STEAM domains. The study sought to investigate young learners’ collective creativity as they engaged in Making projects using arts, crafts and technological tools. Findings from the study suggest that Making activities can enact the development of collective creativity and that there is a statistically significant linear relationship between collective creativity (metacognitive, cognitive and socio-communicative dimensions) and project success.
Keywords: 21st century skills; Collective creativity; Maker culture; Maker movement; Making; STEAM